Компьютерное моделирование реактора для высокотемпературного адиабатического нитрования бензола - Кондратов, Сергей Алексеевич; Красильникова, Анна Александровна (НТУ "ХПИ", 2017)
Рассмотрены две модели реактора высокотемпературного адиабатического нитрования бензола: "мягкая" модель, основанная на кинетике гетерогенного нитрования в условиях идеального перемешивания, и упрощенная ячеечная модель, Обе модели позволяют грубо оценить границы времени пребывания для достижения высокой степени превращения в реакторе вытеснения в процессе высокотемпературного адиабатического нитрования бензола. Модели могут быть использованы при проектировании опытных установок высокотемпературного адиабатического нитрования.

A "soft" model of the ideal tubular reactor with mixing elements for the process of high-temperature adiabatic nitration of benzene in the mixture of HNO₃-H₂SO₄-H₂O has been developed. This model makes it possible to estimate roughly the boundaries of the residence time to achieve a high degree of conversion. The standard model of a tubular piston flow adiabatic reactor in the stationary state was used. The model is based on the kinetic data of heterogeneous nitration under ideal mixing conditions and the parameter that characterizes the delamination. It was shown by modeling that in the range of operating temperatures of nitration of 100-150 °C and a degree of conversion of 0-100%, the density change does not exceed 3% rel. It is possible to regard the density as constant in the first approximation. The upper and lower limits of the values of this parameter can be chosen empirically. A simplified cell model of high-temperature adiabatic nitration was proposed. The model is based on the next assumption. The emulsion in the cell is stratified after mixing. As a result, the average volume fraction of the emulsion in the mixture becomes less than 1. It has been suggested that this amount of emulsion fully reacts in the cell. Next, mixing and transition to the next cell occurs. A satisfactory correspondence between the results of the model calculation and the literature data was demonstrated. The developed models can be used to design research facilities for high-temperature adiabatic nitration to estimate the length of a tubular reactor.
Computer simulation of a reactor for high-temperature adiabatic nitration of benzene
Keywords: реактор идеального вытеснения; математические модели; ячеечная модель; гетерогенное нитрирование; ideal tubular reactor; mathematical models; cell model